Morphological and morphometric analysis of the inferior alveolar canal and mental foramen in black South Africans: A panoramic radiographic study - Ikeoluwa A. Oluwafemi; Nicolene Jooste; Pamela Pillay; Sundika Ishwarkumar-Govender (Translational Research in Anatomy)
Background and objectives: Variations in the route followed by the inferior alveolar canal (IAC) and the position of the mental foramen (MF) could impact the placement of the neurovascular bundle, a vital consideration during mandibular surgeries. This study was conducted to investigate the morphology and the morphometry of the IAC and the position of the MF as seen on panoramic radiographs in a South African population. Methods: A retrospective cross-sectional study was conducted on 200 digital panoramic radiographs. The morphology, i.e., the anteroposterior course, the vertical and horizontal position, and the morphometric parameters of the IAC were obtained and analyzed. The mental foramen position was categorized and analyzed. Results: Elliptic arc canals were the most frequently observed (55.00 %) anteroposterior course (APC) of the IAC. The intermediate position was the most common vertical position (48.30 %) of the IAC. The commonest horizontal relation of the IAC was type 1 (45.50 %), with a statistically significant difference between the right and left sides of the mandible. Many of the MF (50.00 %) were located at Position 4, with a statistically significant difference between the ages of 15–19 and 40–50. The mean measurement of the IAC decreased from the first molar to the third molar, with statistically significant differences between sexes and across age groups. The average diameter of the IAC was about 3–4 mm and was relatively constant. Conclusion: As seen in other populations, most Black South Africans had a favorable APC of the IAC for rehabilitative purposes. Considering the vertical position, most of the canals (51.7 %) were in the high-risk zone (high and low canals), and females had a higher frequency of high canals. Clinicians should expect to find the MF symmetrically in line with the root tip of the second premolars: however, the position of the MF moves posteriorly with advancing age.